Tribological Study of a Non-N, P-Containing Acetic Ester Derivative as Additive in Hydrogenated Oil - Xiong, Liping; He, Zhongyi; Wang, Junxiao; Qiu, Jianwei; Fu, Xisheng (Asian Journal of Chemistry, 2012)
A novel ester derivative, octyl xanthate acetic octcyl xanthate ester (XE) was synthesized and it's tribological behaviours as additive in hydrogenated oil, were evaluated using a four-ball tester. Results show that the compound possesses good antiwear performance, extreme pressure capacity and good friction-reducing property. The action mechanism was estimated through analysis of the worn surface with X-ray photoelectron spectroscopy (XPS) and scanning electron microscope (SEM). The results of XPS and SEM analyses illustrate that the prepared compound as an additive in hydrogenated oil forms a protective film containing ferric sulfide and ferric sulfate compounds on the rubbed surface.